COVID-19 Global Pandemic Lockdown Impact on Visit Nepal Year 2020: A Review - Gautam, Deepak; Khatri, Aarati (The Gaze: Journal of Tourism and Hospitality, 2021)
Tourism sector, a major backbone in revenue generation in Nepal having an immense potentiality is hardly hit by the ongoing COVID-19 pandemic that has suspended Visit Nepal Year 2020, with a theme, an experience of a life-time. This remarkable campaign is also a national development strategy in the tourism history of Nepal which aimed at attracting around 2 million foreigners from all over the world. This article is designed to explore about COVID-19 Pandemic lockdown impacts on tourism industries and Visit Nepal year 2020 Campaign. For these, secondary literature available in Google Scholar, Research Gate and, recently published newspapers were accessed. The result shows that the unprecedented and uncertain lockdown stuck millions of people in their home, lower the economic activities of different sectors of the tourism industry including hotels, homestays, travel and tours, impact on remittance, a collapse of small industries and suspension of mega projects and many more. In addition to this, this paper aims at showcasing a strong correlation between lockdown and tourism industry with perspective from Nepal Tourism Board, Academic practitioner, Tourism Entrepreneurs, Nepal government, ministries, Economist and Analyst to revise the protocols and safety standard of the tourism industry to massively flourish and revive amidst the pandemic and even in the post-pandemic environment.